Indonesian Trade Policy in Adjusting the 2020 WTO’s Trade Policy Review - Putu George Matthew Simbolon; Angel Damayanti (Universitas Muhammadiyah Yogyakarta, 2023)
This article analyzes the Trade Policy Review Body (TPRB) review of Indonesia in 2020, mainly in the agricultural sector, and how Indonesian compliance with the WTO Agreement is helpful for the Trade Policy Review Mechanism (TPRM). This study uses the normative method by gathering primary and secondary legal sources. The 2020 TPRB review perceives that Indonesia has applied untransparent safeguard measures related to its agricultural products, prohibited subsidies, and quantitative restrictions on other WTO member states. However, the Job Creation Law, launched in 2020, can be viewed as a proportional law as it puts imported products in an equivalent position with domestic agriculture or food products. The discussions reveal that Law No 11/2020 aims to balance its national interest with the WTO Agreement and the TPRB review of Indonesian trade policy, mainly in agriculture. With such legal certainty, this article recommends that Indonesia consider the TPRB review in good faith by invoking transparent safeguards, reducing its export subsidies on agricultural products, conducting a persistent report to the Committee on Agriculture, and protecting its public health and morals. The Indonesian government should also conduct text mining to determine its trade policies and deal with international trade uncertainty.